Assessment of Knowledge and Awareness Regarding NBC and Bylaws: A Case Study of Compliance and Awareness in Sundarbazar Municipality, Nepal - Adhikari, Sundar; Sapkota, Prashrit; Khanal, Atit (International Journal on Engineering Technology and Infrastructure Development, 2024)
In Nepal, seismic risks are imminent due to its location on the boundary of the Indian and Eurasian tectonic plates. This study delves into the implementation status of the National Building Code (NBC) in Sundarbazar Municipality, focusing on factors such as Mandatory Rule of Thumb (MRT) compliance, institutional mechanisms, awareness levels, and perspectives. The investigation reveals challenges in the adopted method and institutional structure for building code implementation, particularly stemming from a shortage of staff. Both primary and secondary data sources were utilized, with stakeholders including house owners, local contractors, consultants, and municipal technical personnel providing primary insights. The study uncovers a disparity in awareness levels, with technical personnel exhibiting positive perspectives on building bylaws, while local contractors display unfamiliarity. Drawing on a sample of building permits issued, the evaluation includes Class C and Class B building design drawings, highlighting complexities in the application process for Class B structures. This research signals the need for a reevaluation of the building code implementation strategy in Sundarbazar, emphasizing the importance of addressing knowledge gaps and enhancing institutional capacity. The findings contribute to a nuanced understanding of the challenges hindering effective building code compliance and suggest avenues for future research and Policy adjustments.